P50 Difficult Asthma Clinics: Are They Effective?. (10th November 2014) - Macpherson, I; Fielding, S; Douglas, JG
Abstract : Background: "Difficult asthma" is defined as persistent symptoms and/or frequent exacerbations in patients with a diagnosis of asthma, despite treatment at step 4 or 5 of the BTS/SIGN guidelines 1 . "Difficult asthma" clinics have been set up in many UK hospitals, but there is no published evidence to suggest their effectiveness at reducing exacerbations or hospital admissions. Aims: To determine whether a regional difficult asthma clinic led to a reduction in prescription of oral steroid for exacerbations and a reduction in hospital admissions for asthma. Methods: A retrospective analysis of patients who attended this regional difficult asthma clinic between August 2009 and May 2013 was performed. Medical notes and GP letters were scrutinised to ascertain the number of hospital admissions two years before and two years after the first clinic appointment. For oral steroids, one year before and after was used. To compare these data Wilcoxon tests were used due to the skewed data. Results: For hospital admissions, data was available for 44 patients, mean (SD) age 44.2 (14.1) and 66% female. The median (inter-quartile range (IQR)) number of hospital admissions in the two years prior to clinic was 2 (0, 3) compared to 0 (0, 1) in the two years following clinic visit (p = 0.014). Oral steroid prescription data was available for 54 patients, mean (SD) age 43.5 (14.4), 70% female. The median (IQR) number of oral steroid courses required in the year prior to first clinic appointment was 6 (3.75, 10), which reduced to 2 (0, 4) in the year after first appointment (p < 0.001). Conclusion: Our regional difficult asthma clinic significantly reduced both hospital admissions for asthma two years after first clinic appointment and number of oral steroid prescriptions one year after first clinic appointment. This study, although small, highlights the benefit of such clinics to patients and the potential for the reduction in use of NHS resources. They should be encouraged in all major centres. Reference: Prys-Picard CO, Campbell SM, Ayres JG, Miles JF, Niven RM. Consensus Difficult Asthma Consortium UK. Defining and investigating difficult asthma: developing quality indicators. Respiratory Medicine 2006;100(7):1254–61